Penyelesaian Pembebanan Hak Tanggungan Atas Tanah Yang Belum Bersertifikat Ditinjau Dari Undang-Undang Nomor 4 Tahun 1996: Studi Kasus Pada PT. Bank Pembangunan Daerah Jawa Barat Dan Banten TBK Di Jakarta - Kalis Sry Handayani; Imma Rahmani Hasanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The research examines the legal aspects of encumbering land that is not yet certified with a security right (Hak Tanggungan/HT) as a bank loan guarantee, along with the legal protection for creditors in case of debtor default. Legally, the encumbrance of HT on uncertified land is possible according to Article 10 paragraph (3) of the HT Law (UUHT). However, the results of the normative juridical and empirical study indicate that implementation faces administrative constraints , such as the lengthy certification process, lack of resources in the land office, and the uncertainty of registration time. This situation potentially weakens the legal protection for creditors before the HT is officially registered. Therefore, the research recommends mitigation steps for banks , including ensuring the HT registration process and land certification are executed concurrently with the drafting of the Deed of Granting Security Right (APHT), and strengthening the role of the notary and PPAT (Land Deed Officials) to guarantee the legality and legal certainty of the collateral encumbrance.